2018
DOI: 10.3389/fmicb.2018.01652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Infusion With Sodium Butyrate on Colonic Microbiota, Intestinal Development- and Mucosal Immune-Related Gene Expression in Normal Growing Pigs

Abstract: This study aimed to investigate effects of intravenous infusion with sodium butyrate (SB) on colonic microbiota, intestinal mucosal immune and intestinal development in normal growing pigs. Twelve crossbred barrows (Duroc × Landrace × Large White) fitted with a medical polyethylene cannula via internal jugular vein were daily infused with 10 ml SB (200 mmol/l) or the same volume of physiological saline for 7 days. Results showed that SB infusion had no effects on the short-chain fatty acids concentrations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
1
15
0
1
Order By: Relevance
“…However, our study showed the opposite result that the change in gut microbiota composition significantly decreased LPS content in chyme in high gelatinized starch diet group, compared with control group, which was beneficial to the gut health to a certain extent. Butyrate is an important energy source for gut enterocytes (Chen et al, 2018), and it is mainly from butyric acid-producing bacteria in gut (Hamer et al, 2008). Lack of butyric acid can result in gut permeability increase (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study showed the opposite result that the change in gut microbiota composition significantly decreased LPS content in chyme in high gelatinized starch diet group, compared with control group, which was beneficial to the gut health to a certain extent. Butyrate is an important energy source for gut enterocytes (Chen et al, 2018), and it is mainly from butyric acid-producing bacteria in gut (Hamer et al, 2008). Lack of butyric acid can result in gut permeability increase (Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have focused on how the nutrients in the diet affect gut health or body health by reshaping the gut microbiota. Resistant starch in diet give rise to substantial changes in the microbiome and in fermentation products (Kleessen et al, 1997;Wang et al, 2002;Warren et al, 2018), and these fermentation products help improve the immune system (Chen et al, 2018). High levels of fat in diet change the gut microbial community, particularly by increasing the ratio of Firmicutes to Bacteroidetes to affect health of the host (Okazaki et al, 2016), and high-fat diets result in obesity and inflammation by destroying the structure of the gut microbiota (De Lartigue et al, 2011;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate increased the expression of claudin‐3, claudin‐4 and restored the reduction in the abundance of these proteins caused by LPS challenge (Yan and Ajuwon ). Chen et al () reported that parenteral butyrate treatment increased the mRNA expression of ZO‐1 and occludins in the colon mucosa of piglets. Sodium butyrate improved the intestinal barrier function and maintained the intestinal mucosa intact (Fang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the previous studies. Parenteral supplemented with sodium butyrate in a manner of intravenous infusion also significantly decreased the gene expression of colonic proinflammatory cytokines IL-6, IL-18, IL-12p40, and TNF-α, but increased the expression of intestinal development-related genes ZO-1 , occluding, and EGF ( Chen et al, 2018b ). Moreover, butyrate ameliorated Clostridium difficile -induced colonic inflammatory responses as indicated by significantly decreased inflammatory cytokines such as IL-1β, IL-6, and CXCL-1 ( Fachi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%